Characterization of SR-B2a and SR-B2b genes and their ability to promote GCRV infection in grass carp (Ctenopharyngodon idellus). (November 2021) - Li, Yangyu; Huang, Rong; Chen, Liangming; Li, Yangyang; Li, Yongming; Liao, Lanjie; He, Libo; Zhu, Zuoyan; Wang, Yaping
Abstract: Scavenger receptor class B type 2 (SR-B2) is a pattern recognition receptor involved in innate immunity in mammals; however, the immunological function of SR-Bs in fish remains unclear. In this study, the full-length cDNA sequences of SR-B2a and SR-B2b from grass carp ( Ctenopharyngodon idellus ) were cloned and designated as CiSR-B2a and CiSR-B2b . Multiple alignments and phylogenetic analyses deduced that CiSR-B2a and CiSR-B2b had the highest evolutionary conservation and were closely related to the zebrafish ( Danio rerio ) homologs, DrSR-B2a and DrSR-B2b, respectively. Both CiSR-B2a and CiSR-B2b were expressed in all the tested tissues, with the highest expression levels found in the hepatopancreas. In Ctenopharyngodon idellus kidney cells (CIK), CiSR-B2a and CiSR-B2b were mainly located in the cytoplasm, and a small amount located on the plasma membrane. After challenge with Grass Carp Reovirus (GCRV), the expression of CiSR-B2a and CiSR-B2b were significantly upregulated in the spleen (about 10.27 and 27.19 times higher than that at 0 day, p < 0.01). With CiSR-B2a or CiSR-B2b overexpressed in CIK, the relative copy number of GCRV in the cells was both significantly increased compared to that in the control group, indicating that CiSR-B2a and CiSR-B2b may be important proteins during the infection processes of GCRV. Highlights: 1. Scavenger receptor class B type 2 ( CiSR-B2a and CiSR-B2b ) were characterized in grass carp (Ctenopharyngodon idella ). 2. CiSR-B2a and CiSR-B2b mRNA expressions were obviously up-regulated in spleen post GCRV infection. 3. CiSR-B2a and CiSR-B2b were mainly located in the cytoplasm, and a few on the plasma membrane. 4. The relative copy number of GCRV in CIK cells were upregulated post overexpression of CiSR-B2a and CiSR-B2b, respectively.